Collins primary focus: grammer and punctuation pupil book 1 - Fidge, Louis; Lindsay, Sarah (Collins / Peak London /Karachi, 2014)
Collins Primary Focus: Grammar and Punctuation Teacher's Guide 1 contains teaching notes for every unit: learning objectives, matched to APP, definitions, background information, shared, guided and independent writing activities, group and pair work ideas, speaking and listening activities, support and extension worksheets.